LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF YELLOWSTRIPE SCADS Selaroides leptolepis IN SUNDA STRAIT - Putri Sapira Ibrahim; Isdradjad Setyobudiandi; . Sulistiono (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Yellowstripe scad Selaroides leptolepis is important product of small pelagic fishery resources in Java Sea. This fish also has high economic value and mostly captured by fisherman. The purpose of this study was to determine length weight relationship and condition factor of yellowstripe scads Selaroides leptolepis in Sunda Strait. Sampling was conducted from April to August 2015 with stratified random sampling method from catch landed at Pelabuhan Perikanan Pantai (PPP) Labuan, Banten. The results showed that 757 fish captured consists of 337 females and 420 males. The length weight relationship was W= 0.00004L2.7176 for female and W= 0.00003L2.7871 for male. The results indicated that the length weight relationship was highly correlated (r > 95%). the relative condition factors of fish varied from 1.0061-1.1926, of which females were generally in better condition than the males. Keywords: condition factor, length-weight relationship, yellowstripe scads, Sunda Strait